4-Methyl-N-(4-nitrobenzylidene)piperazin-1-amine - Kavitha, Channappa N. (International Union of Crystallography, 2013)
In the title compound, C(12)H(16)N(4)O(2), the piperazine ring is in a slightly distorted chair conformation. In the molecule, the mean plane of the nitro group is twisted by 8.0 (3)° from that of the benzene ring. Also, the mean plane of the 2-nitrobenzyl ring is twisted slightly from that of the piperazine ring, with an N—N=C—C torsion angle of −176.24 (11)°. In the crystal, pairs of weak C—H⋯O interactions link the molecules into dimers approximately along [010].